Role of Laparoscopy in the Management of Neonatal Ovarian Cysts - Vijay C Pujar; Shirin S Joshi; Yeshita V Pujar; Hema A Dhumale (EL-Med-Pub, 2014)
Aim: Ovarian cysts in the newborn period are simple cysts which resolve on their own. Complications like torsion leading to loss of ovarian units are well documented. Surgical treatment should always be performed in a way to protect the ovaries and to ensure future fertility. The aim of this study was to study the safety and efficacy of laparoscopic management of neonatal ovarian cysts. Materials and Methods: Neonates with ovarian cysts over last 6 years were retrospectively studied. Thirty seven ovarian cysts were detected antenatally and 32 of them persisted postnatally. All babies were asymptomatic. Nine babies with cyst size more than 5cms underwent laparoscopic deroofing, fenestration or cystectomy; the rest 23 babies were managed conservatively. Sonographic monitoring was done at monthly interval for change in contents, echogenicity of walls and features of torsion. Follow up was done with USG at 3 and 6 months and MRI after 1 year. Results: No procedure related complications were seen in the laparoscopy group and no loss of ovarian units were seen in 1 year follow-up. In the observation group, cysts resolved in 3- 12 months period. Three babies developed complications and 4(17%) ovarian units were lost. Conclusion: Ovarian cysts are the most frequent among intra-abdominal cysts in newborns. Neonatal ovarian cysts are known to resolve spontaneously. Laparoscopic management of these cysts is safe and efficacious even in neonatal age and should be the treatment of choice when indicated.